Development of Arabic Interactive Learning Media Assisted by Kodular for Grade VIII at Islamic Junior High School - Wicaksana, M. Tegar; Erlina (WISE Pendidikan Indonesia, 2023)
This research is a research and development of interactive learning media in Arabic with codular assistance for class VIII of Madrasah Tsanawiyah. This study aims to find out how the development, feasibility, student responses and effectiveness of codular-assisted Arabic interactive learning media. This research method is research and development (R&D) based on a 4D model consisting of definition, design, development and dissemination. Before media is used, it is verified by two media and material experts. Subjects of this study were class VIII students of MTs Guppi 2 Tanjung Karang (maximum 20 students) and MTs NU Tanjung Karang (maximum 20 students). Survey data were obtained through interview techniques, questionnaires, tests and documentation. Rating results based on the Media Expert Validation Questionnaire for this Cordura-based Arabic interactive learning media are in the valid category with a decent category average score of 98%. The material expert's assessment of this codular-assisted Arabic interactive learning media obtained an average score of 98% with a decent category. Based on calculations using the t-test, researchers obtained the results of research data in MTs Guppi 2 Tanjung Karang with a value = 12.55 and a value = 1.27 at a significant level = 0.05 with the results of the comparison with is 12.55>1.27. Then the researchers obtained the results of research data at MTs NU Tanjung Karang with a value = 10.38 and a value = 2.88 at a significant level = 0.05 with the results of a comparison with is 10.38>2.88. The results of the two research data showed significant results between before using learning media and after using learning media. So by looking at the results above, this codular-assisted Arabic interactive learning media has shown high effectiveness in improving student learning outcomes.